Brain death and tissue and organ transplantation: the understanding of medical students - dos Reis, Flávio Pola (Associação Brasileira de Medicina intensiva, 2013)
OBJECTIVE: To evaluate the level of knowledge of medical students about transplantation and brain death. METHODS: An anonymous self-administered questionnaire answered by medical students from the first through the sixth year that was based on information from the Associação Brasileira de Transplante de Órgãos e Tecidos, the Registro Brasileiro de Transplantes and the resolution that defines the criteria for brain death. RESULTS: Of the 677 medical students asked, 310 (45.8%) agreed to answer the questionnaire. In total, 22 (7.0%) subjects were excluded. Of the students who participated, 41.3% reported having already attended a class on organ transplantation and 33% on brain death; 9.7% felt able to diagnose brain death (p<0.01); only 66.8% indicated the kidney as the most transplanted solid organ in Brazil. CONCLUSION: The level of knowledge of medical students at this institution regarding brain death and transplantation is limited, which may be the result of an inadequate approach during medical school.